Research of Cone Pulley Thrust Balance Mechanism of CVT under No Load Condition - Zhou Yunshan; Ma Chicheng; Zhang Feitie (Jixie chuandong)
Under condition of zero torque,speed ratio is different even if continuously variable transmissions（ CVT） have the same control pressure. In order to investigate the phenomena,the thrust balance model and its impact factors is researched under no load condition. The theoretical balance thrust ratio is calculated under no load condition. Through test bench experiment,impacts on balance thrust ratio from speed ratio,secondary pressure and primary pulley speed are researched. The theoretical model shows that balance thrust is proportional to the ratio between primary and secondary working wrap angle,and this analysis results is verified through test bench experiment. Other experimental results are as follows. Speed ratio impacts thrust ratio significantly through a monotonically decreasing relationship and this relationship is not affected by secondary pressure. Impacts from primary pulley speed can be ignored. The balance mechanisms of thrust ratio under no load condition is researched and theoretical and experimental basis for further research on transmission principles between CVT and metal belt is provided.